Identification Des Zones Potentielles De Recharge Des Aquifères Fracturés Du Bassin Versant Du N’zo (Ouest De La Côte d’Ivoire) : Contribution Du SIG Et De La Télédétection - Oularé, Sékouba; Adon, Gnangui Christian; Akpa, Lucette You; Saley, Mahaman Bachir; Kouamé, Fernand Koffi; Therrien, René (European Scientific Journal, ESJ, 2017)
In a watershed one of the most important data is recharge because it is the main groundwater supply. Recharge is however, a difficult parameter to calculate due to its variability. The objective of this study is to propose a method of identifying potential recharge zone which is applicable to large watersheds. The study area is the N’zo watershed located in the West of Côte d’Ivoire. It covers an area of 4,300 km2 . The water supply of the population is essentially ensured by the fractured aquifers which are the regional aquifers.The data used in this study are classified in two groups1) the cartographic data are composed of geological soil and drainage maps; and 2) data from remote sensing which consist of slope, land use and fractures maps. These data are combined through a multi-criteria analysis to facilitate spatial analysis and identification of potential recharge areas. The results indicate that potential areas of high recharge account for about 20% of the total watershed area. They are mainly located in the south and center and appear fragmented in the north of the watershed.